Heme Induces IL-6 and Cardiac Hypertrophy Genes Transcripts in Sickle Cell Mice - Gbotosho, Oluwabukola T.; Kapetanaki, Maria G.; Ghosh, Samit; Villanueva, Flordeliza S.; Ofori-Acquah, Solomon F.; Kato, Gregory J. (Frontiers in Immunology, 2020)
Emerging data indicate that free heme promotes inflammation in many different disease settings, including in sickle cell disease (SCD). Although free heme, proinflammatory cytokines and cardiac hypertrophy are co-existing features of SCD, no mechanistic links between these features have been demonstrated. We now report significantly higher levels of IL-6 mRNA and protein in hearts of the Townes sickle cell disease (SS) mice (2.9-fold, p≤0.05) than control mice expressing normal human hemoglobin (AA). We find that experimental administration of heme 50 µmoles/kg body weight induces IL-6 expression directly in vivo and induces gene expression markers of cardiac hypertrophy in SS mice. We administered heme intravenously and found that within three hours plasma IL-6 protein significantly increased in SS mice compared to AA mice (3248±275 vs 2384±255 pg/ml, p≤0.05). In the heart, heme induced a 15-fold increase in IL-6 transcript in SS mice heart compared to controls. Heme simultaneously induced other markers of cardiac stress and hypertrophy, including atrial natriuretic factor (Nppa; 14-fold, p≤0.05) and beta myosin heavy chain (Myh7; 8-fold, p≤0.05) in SS mice. Our experiments in Nrf2-deficient mice indicate that the cardiac IL-6 response to heme does not require Nrf2, the usual mediator of transcriptional response to heme for heme detoxification by heme oxygenase-1. These data are the first to show heme-induced IL-6 expression in vivo, suggesting that hemolysis may play a role in the elevated IL-6 and cardiac hypertrophy seen in patients and mice with SCD. Our results align with published evidence from rodents and humans without SCD that suggest a causal relationship between IL-6 and cardiac hypertrophy.